POLYCYSTIC OVARY SYNDROME (PCOS)–AN OVERVIEW - C., Muhas; M., Nishad K.; P., Ummunnoora K.; K., Jushna; V., Saheera K.; P., Dilsha K. (International Journal of Current Pharmaceutical Research, 2018)
Polycystic ovary syndrome (PCOS) is one of most common female endocrine disorder that affects 6-15% of the female population. Women with PCOS have a hormonal imbalance and metabolism problems that may affect their overall health and appearance. Androgen excess and insulin resistance are currently recognized to be responsible for much of the phenotypic presentation, though insulin resistance is far from universally present. It is characterized by irregular menstrual cycle, acne and also associated with type-2 diabetes mellitus and cardiovascular disease. Efficient management of PCOS provides a prospective window of opportunity to avoid the risk of associated complications. Treatment is broadly aimed at tackling (IR), effects of hyperandrogenism, irregular menstruation, and infertility. This review article mainly deals with the etiology, pathophysiology, diagnosis and management of Polycystic ovary syndrome.